Diuretic Combination Therapy in Acute Heart Failure: An Updated Review - Villaschi, Alessandro; Pellegrino, Marta; Condorelli, Gianluigi; Chiarito, Mauro (Current Pharmaceutical Design, 2024)
Loop diuretics are the cornerstone of decongestive therapy in patients presenting with acute heart failure and have been extensively studied in randomized clinical trials. Therefore, in current guidelines, they are the only drug with a class I recommendation to treat signs and symptoms of congestion when present. However, the percentage of patients achieving successful decongestion is suboptimal, and diuretic resistance frequently develops. Patients with a poor response to loop diuretics and those discharged with residual signs of congestion are characterized by a worse prognosis over time. Recently, a renovated interest in different diuretic classes sprouted among heart failure researchers in order to improve decongestion strategies and ameliorate short- and long-term clinical outcomes. Randomized clinical trials investigating associations among diuretic classes and loop diuretics have been performed but yielded variable results. Therefore, despite initial evidence of a possible benefit from some of these compounds, a definite way to approach diuretic resistance via diuretic combination therapy is still missing. The aim of this review is to summarize current clinical evidence on the use of diuretic combination therapy in patients with acute heart failure and to suggest a possible approach to avoid or counteract diuretic resistance.
Keywords: Acute heart failure